Effects of white yolk concentration on maturation, fertilization, and blastocyst development of bovine embryos produced in vitro - Quam, Jessica (My University, 2004)
Most in vitro embryo production (IVP) systems use some form of bovine sera in media. The most commonly used sera in maturation of bovine oocytes is fetal calf serum. A potential problem arising from this practice is disease transfer to the embryo as the sera is coming from the same species as the embryo. A potential substitute (white yolk from avian eggs) derived from a different order of animals could ameliorate this problem. This study was done to determine if white yolk plasma is a suitable supplement to use in the maturation of bovine embryos. Eight replications were done: a control (10% fetal calf serum), and three treatments, replacing fetal calf serum with 5%, 10% or 15% white yolk plasma. Data on fertilization, cleavage, and blastocyst development rate and post freezing/thawing survival were collected. There were no significant differences among treatments for fertilization, cleavage, blastocyst development, or post freezing/thawing survival indicating that white yolk is a suitable substitute for fetal calf serum in bovine oocyte maturation systems
7 p.
Keywords: Animal Sciences